Effect of sustained use of platelet aggregation inhibitors on post‐endoscopic sphincterotomy bleeding. Issue 6 (27th March 2014) - Lee, Min Geun; Kim, Jaihwan; Lee, Sang Hyub; Lee, Ban Seok; Lee, Seung June; Lee, Yoon Suk; Cha, Byung Hyo; Hwang, Jin‐Hyeok; Ryu, Ji Kon; Kim, Yong‐Tae
<x xml:space="preserve">Abstract</x> Background and Aim The effect of platelet aggregation inhibitors (PAI) on post‐endoscopic sphincterotomy (ES) bleeding in patients who cannot discontinue PAI for sufficient time in urgent conditions has not been identified. The present study analyzed the effect of sustained use of PAI on post‐procedural bleeding in patients undergoing ES. Methods A total of 762 patients were grouped into one of the following groups: no‐PAI group (n = 601), continuation group (n = 132), and withdrawal group (n = 29). The continuation group included sustained PAI therapy (sustained user, n = 49) or those in whom therapy was interrupted <7 days prior to ES (non‐sustained user, n = 83). The primary outcome was defined as the incidence, type, and severity of post‐ES bleeding among groups. Results There were no significant differences between incidence, type, or severity of post‐ES bleeding in the three groups. Among 132 patients with continued use of PAI, there was no significant difference regarding incidence and severity of bleeding according to sustained or non‐sustained use (P = 0.071 and P = 0.086, respectively). However, post‐ES delayed bleeding was more frequent in sustained PAI users than in non‐sustained users (7/49, 14.3% vs 2/83, 2.4%) and was significantly associated with sustained PAI therapy in the continuation group (P = 0.013). Conclusion Sustained use of PAI without interruption until ES might increase the risk of delayed bleeding.